The role of efferocytosis in inflammatory bowel disease - Yi-Qian Liu; Zhan-Zhan Li; Yong-Li Han; Qing-Bo Wang (Frontiers in Immunology)
Efferocytosis is the process by which various phagocytes clear apoptotic cells. In recent years, an increasing body of evidence has emphasized the importance of efferocytosis in maintaining internal homeostasis. Intestinal macrophages play a crucial role in modulating intestinal inflammation and promoting tissue repair. Inflammatory bowel disease (IBD) is a chronic, progressive, and relapsing condition, primarily marked by the presence of ulcers in the digestive tract. The exact mechanisms underlying IBD are not yet fully understood, and current treatment approaches mainly aim at repairing the damaged intestinal mucosa and reducing inflammatory responses to ease symptoms.This article provides new perspectives on IBD treatment and clinical management by examining the expression of macrophage efferocytosis-related molecules, the effects of efferocytosis on IBD development, the various roles of macrophage efferocytosis in IBD, and treatment strategies for IBD that focus on efferocytosis.